C. elegans Methods and Applications - Biron, David.; Biron, David.; Haspel, Gal.; Haspel, Gal. (Methods in Molecular Biology,, 2015)
The aim of this volume is to provide a step-by-step guide for implementing a selection of novel techniques in the lab. Each protocol in this volume is presented as a standalone chapter, specifically geared towards addressing practical needs without presuming prior knowledge of the technique at hand. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, C. elegans: Methods and Applications, Second Edition aims to ensure successful results in the further study of this dynamic field.